Analisis Keputusan Pembelian Konsumen Ditinjau dari Kualitas Produk Lokasi dan Promosi Terhadap Busana Batik di Pusat Grosir Solo - Deviana Putri; Burhanuddin Burhanuddin; Ratna Damayanti (ITB AAS INDONESIA Surakarta, 2019)
This study aims to prove and know the quality of products, locations and promotions simultaneously or partially towards the decision to purchase batik clothing. This type of research is a quantitative descriptive study, the population of this study is that all consumers who have bought batik clothing in PGS are infinite in number and the sampling method uses purposive sampling technique. The sample used was 100 respondents. The analytical method used is the method of multiple linear regression analysis. The method of data collection is by distributing questionnaires or questionnaires. The results showed that the F test of product quality, location and promotion had a simultaneous and significant effect on purchasing decisions on batik clothing products at PGS, while the results of the t test showed that product quality had a positive and significant effect on purchasing decisions on batik clothing products at PGS, locations not influential and not significant towards purchasing decisions, promotion of influential products has a positive and significant effect on purchasing decisions on batik clothing products at PGS. The results of the coefficient of determination show that the independent variable (X) product quality, location and promotion has an influence of 35.4% on the dependent variable (Y) purchasing decisions on batik clothing products at PGS. The most influential variable is product quality. Keywords: purchasing decisions, product quality, location, promotion